Depletion of reduction potential and key energy generation metabolic enzymes underlies tellurite toxicity in Deinococcus radiodurans. Issue 1 (5th December 2014) - Anaganti, Narasimha; Basu, Bhakti; Gupta, Alka; Joseph, Daisy; Apte, Shree Kumar
<x xml:space="preserve">Abstract</x> Oxidative stress resistant Deinococcus radiodurans surprisingly exhibited moderate sensitivity to tellurite induced oxidative stress (LD50 = 40 μM tellurite, 40 min exposure). The organism reduced 70% of 40 μM potassium tellurite within 5 h. Tellurite exposure significantly modulated cellular redox status. The level of ROS and protein carbonyl contents increased while the cellular reduction potential substantially decreased following tellurite exposure. Cellular thiols levels initially increased (within 30 min) of tellurite exposure but decreased at later time points. At proteome level, tellurite resistance proteins (TerB and TerD), tellurite reducing enzymes (pyruvate dehydrogense subunits E1 and E3), ROS detoxification enzymes (superoxide dismutase and thioredoxin reductase), and protein folding chaperones (DnaK, EF‐Ts, and PPIase) displayed increased abundance in tellurite‐stressed cells. However, remarkably decreased levels of key metabolic enzymes (aconitase, transketolase, 3‐hydroxy acyl‐CoA dehydrogenase, acyl‐CoA dehydrogenase, electron transfer flavoprotein alpha, and beta) involved in carbon and energy metabolism were observed upon tellurite stress. The results demonstrate that depletion of reduction potential in intensive tellurite reduction with impaired energy metabolism lead to tellurite toxicity in D. radiodurans.